2013
DOI: 10.1007/s10548-013-0319-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dimensional Dynamics of Resting-State Cortical Activity

Abstract: Endogenous brain activity supports spontaneous human thought and shapes perception and behavior. Connectivity-based analyses of endogenous, or resting-state, functional magnetic resonance imaging (fMRI) data have revealed the existence of a small number of robust networks which have a rich spatial structure. Yet the temporal information within fMRI data is limited, motivating the complementary analysis of electrophysiological recordings such as electroencephalography (EEG). Here we provide a novel method based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 74 publications
12
68
0
Order By: Relevance
“…These findings add to an increasing body of literature suggesting that neuronal interactions result in both in phase and amplitude coupling (Bayraktaroglu et al, 2013;Chawla et al, 1999Chawla et al, , 2000Daffertshofer and van Wijk, 2011;Mehrkanoon et al, 2014). On the other hand, amplitude and phase coupling are considered to have different causes and putative functions (Engel et al, 2013), and to operate at different time scales .…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…These findings add to an increasing body of literature suggesting that neuronal interactions result in both in phase and amplitude coupling (Bayraktaroglu et al, 2013;Chawla et al, 1999Chawla et al, , 2000Daffertshofer and van Wijk, 2011;Mehrkanoon et al, 2014). On the other hand, amplitude and phase coupling are considered to have different causes and putative functions (Engel et al, 2013), and to operate at different time scales .…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, envelope correlation of resting-state MEG revealed a broad range of carrier frequencies , with slight variations between cortical regions (Brookes et al, 2011;Hipp et al, 2012). These findings suggest that brain networks do not generally display pure rhythms within distinct frequency bands-mostly generated in restricted neuronal circuits-but a coalescence of rhythms (Mantini et al, 2007;Mehrkanoon et al, 2014). When comparing to connectivity with other voxels at the same physical distance, we found that bilateral coupling was significantly higher at specific frequencies, which was dependent on the cortical region.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…While this gives access to a rich amount of information, one remaining issue is how to combine scales into a concise and meaningful summarizing measure. Recent approaches in EEG analysis have employed a combination of windowed Fourier analysis and principal component analysis (PCA) for that purpose (Mehrkanoon et al, 2014).…”
Section: Resultsmentioning
confidence: 99%